Efektivitas Model Pembelajaran Discovery Learning dan Problem Based Learning (PBL) Berbantuan GeoGebra Terhadap Kemampuan Pemecahan Masalah Siswa - Anindhitya, Anindhitya; Shodiqin, Ali; Prayito, Muhammad (Universitas PGRI Semarang, 2026)
This study aims to determine the effectiveness of Discovery Learning and Problem Based Learning (PBL) learning models assisted by Geogebra on students' problem solving skills. The research design used is True Experimental Design with the form of Posttest Only Control Design. The research population consisted of all eighth-grade students at MTs Matholiul Anwar Sarimulyo. The sample was taken using cluster random sampling, with three classes selected: experiment class I using GeoGebra-assisted discovery learning, experiment class II using GeoGebra-assisted problem-based learning, and the control class using conventional learning. Data analysis was conducted in several stages, including a prerequisite test covering normality and homogeneity tests, hypothesis testing using one-way analysis of variance (One Way ANOVA) to compare the average problem-solving abilities between groups, post-hoc testing using the Scheffe method if significant differences were found, simple linear regression testing to examine the effect of activity on problem-solving abilities, and analysis of student learning completeness individually and classically. The results showed that: (1) There is a difference in the average problem solving ability of students with Geogebra-assisted Discovery Learning model, Geogebra-assisted Problem Based Learning model and Conventional model. (2) The problem solving ability of students using the Geogebra-assisted Discovery Learning model is better than the problem solving ability of students using the conventional model. (3) The problem solving ability of students using the Geogebra-assisted Problem Based Learning model is better than the problem solving ability of students using the conventional model. (4) There is no difference in the average problem solving ability of students using the Discovery Learning model and Geogebra-assisted Problem Based Learning. (5) There is an effect of activeness on the problem solving ability of students using the Discovery Learning and Problem Based Learning models assisted by Geogebra. (6) Students with Geogebra-assisted Discovery Learning and Geogebra-assisted Problem Based Learning learning models have been completed individually and have not been completed classically.